Peran Mediasi Kepuasan Kerja dalam Meningkatkan Kinerja : Studi pada Pegawai Pengawas Ketenagakerjaan Korwil II Malang (Jurnal Ekonomi dan Manajemen, 2023)
This study aims to analyze the role of job satisfaction as a mediator of the influence of leadership and work motivation on the performance of labor inspectors at Korwil II Malang, East Java Province. The research method used is quantitative with an explanatory research approach, involving a population of 32 labor inspectors with saturated sampling techniques. Data were analyzed using path analysis. The results show that leadership and work motivation significantly influence job satisfaction and employee performance. Furthermore, job satisfaction mediates the influence of leadership and work motivation on employee performance. The implications of this study emphasize the importance of participative leadership styles and the provision of extrinsic motivation to increase job satisfaction, which ultimately leads to improved performance of labor inspectors.